Prevalence Of Metabolic Syndrome and Its Associated Factors Among Thai Police Officers – A Population-Based Study - Mahesh Gurung; Runyawan Chotenimitkhun; Kasem Ratanasumawong; Bundit Prommete Prommete; Wichai Aekplakorn (Siriraj Medical Journal, 2023)
Objective: The prevalence of Metabolic Syndrome (MetS) in Thai police officers is unknown. This study aims to accurately determine the prevalence of MetS in this population compared to the Thai general population.